An improved accuracy of web service selection based on multi-criteria decision making and web service modeling ontology - Khezrian, Mojtaba, 1983- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Thesis (Doktor Falsafah, Bidang Penyelidikan: Sains Komputer)) - Universiti Teknologi Malaysia, 2013